A Journey in Leadership - Robert J. Shoop (Educational Considerations, 2009)
In 1997, two faculty members at Kansas State University began the process of creating something special and distinctive that never existed before.
Keywords: millennium; instructional; Educational Leadership; interactive; Concepts; interdisciplinary